Molecular epidemiology of trimethoprim-resistant Shigella boydii serotype 2 strains from Bulgaria. - Bratoeva, M P (1992)
In 1990 an increased number of strains of Shigella boydii serotype 2 were isolated from different regions of Bulgaria. Strains were reported as sporadic, although they showed identical phenotypic characteristics, including resistance to ampicillin, carbenicillin, streptomycin, sulfonamide, tetracycline, ticarcillin, and trimethoprim. The objective of this study was to determine the genetic relatedness of the strains and the mechanism of their antimicrobial resistance. Plasmid fingerprinting showed an identical pattern for 23 of 25 of the selected strains. All 25 strains tested transferred their resistances en bloc to an Escherichia coli recipient. Transconjugants contained a 112-kb R plasmid which carried all the resistance genes, including that conferring type I dihydrofolate reductase-mediated trimethoprim resistance (MIC greater than 2,000 micrograms/ml). Riboprobe analysis showed identical restriction length fragment polymorphisms, suggesting a highly conserved genome. All findings indicate that strains of S. boydii serotype 2 isolated in 1990 from different regions of Bulgaria were highly related genetically and can be considered representatives of a single bacterial clone. The presence of an R plasmid and selection pressure because of the usage of antimicrobial agents, particularly trimethoprim, have likely facilitated the spread of the clone throughout the country.